Pseudo-Zeno : anonymous philosophical treatise - Pseudo-Zeno. (Philosophia Antiqua, 2000)
The Anonymous Philosophical Treatise is here presented to the western world for the first time. It is a philosophical treatise of the Late Antique period, written in about the sixth century C.E. The author was a Christian, but he utilized pagan philosophical sources. Thus this is one of the latest writings of ancient philosophy, and as such is of very considerable interest and importance. The Anonymous Philosophical Treatise was preserved only in Armenian. It was published first half-a-century ago in Armenian and in Russian translation, but is barely known to western scholarship. Here a new edition is presented, prepared on computer, together with critical apparatuses, translation and commentary. A variety of tools for the study of the text are included: a concordance, a word list of the English translation, triliteral tables of Armenian - Greek - English technical terminology and more.